Relationship of dental maloclusion with body position and plant footprint in a group of aymaras teenagers - Inquilla Apaza, Gisenia Pilar (2017)
Objective: To determine the relationship between Class II and III dental malocclusion with body posture and plantar footprint in a group of Aymara adolescents. Materials and Methods: A cross-sectional, cross-sectional study was conducted in a non-probabilistic sample for the convenience of 58 schoolchildren aged 14 to 17 selected by inclusion criteria (29 with class II malocclusion and 29 with class III malocclusion). The determination of the malocclusion was done by means of the clinical observation and model study, the assessment of body posture was performed through clinical and photographic inspection, evaluation of the plantar footprint was performed by clinical inspection using the formula proposed by Hernández Corvo. Data processing and statistical analysis was performed through the proportion test in the Minitab Statistical Program version 17. Results: Of 81 adolescents with class II and III malocclusion, 81.0% presented abnormal posture, 19.0 % normal posture; 70.7% abnormal plantar footprint and 29.3% normal plantar footprint. Conclusions: There is a high frequency of abnormal posture (scoliosis, kyphosis and kyphoscoliosis); and abnormal plantar footprint in the Aymaras adolescents from 14 to 17 years of age, however, there is no significant statistical relationship between Class II and Class III malocclusion with body posture types and plantar footprint types.